Health care professionals' views on discussing sexual wellbeing with patients who have had a stroke: a qualitative study - Mellor, R; Greenfield, S; Dowswell, G; Sheppard, J; Quinn, T; McManus, R (Public Library of Science, 2013)
Objectives To examine the experiences of health care professionals discussing sexual wellbeing with patients who have had a stroke. Design In-depth qualitative interview study with purposive sampling and thematic analysis. Participants 30 health care professionals purposively recruited to include different roles and settings along the stroke patient pathway in secondary and primary care. Setting Two hospitals and three general practices in the West Midlands, UK. Results Sexual wellbeing was a topic that participants did not raise with patients and was infrequently raised by patients. Barriers to raising discussion were on four levels: structural, health care professional, patient, and professional-patient interface. Barriers within these levels included: sexual wellbeing not present within hospital stroke policy; the perception that sexual wellbeing was not within participants' role; participants' concern that raising the issue could cause harm to the patient; and the views that discussion would be inappropriate with older people or unimportant to women. Resources exist to aid discussion but many participants were unaware of them, and most of those that were, did not use them routinely. Conclusions Participants lacked motivation, ownership, and the confidence and skills to raise sexual wellbeing routinely after stroke. Similar findings have been reported in cancer care and other taboo subjects such as incontinence potentially resulting in a sub-optimal experience for patients. Normalisation of the inclusion of sensitive topics in discussions post-stroke does not seem to need significant structural intervention and simple changes such as information provision and legitimisation through consideration of the issue in standard care policies may be all that is required. The experiences recounted by professionals in this study suggest that such changes are needed now.